Education and training for dental leadership – A case study of the Senior Dental Leadership programme. (August 2019) - Bedi, Raman; Wordley, Valerie
Abstract: Leadership training in dentistry is equally as important as gaining clinical skills. The dental profession must urgently develop young dental leaders, so the profession is able to transform poor oral health. The Senior Dental Leadership programme demonstrates how leadership, mentorship and networking can produce strong dental leaders who have significantly improved oral health in low-income countries.